Influence of heat treatment condition on the stress corrosion cracking properties of low pressure turbine blade steel FV520B - Naicker, Leebashen (Centre for Materials Engineering, 2017)
Stress corrosion cracking (SCC) is a corrosion phenomenon which continues to plague the power generating industry especially in low pressure (LP) steam turbine blades operating in the phase transition zone. An investigation has therefore been conducted to examine the effect of heat treatment condition on the microstructure, mechanical properties and SCC properties of one such LP turbine blade material, FV520B, used in the steam turbines of coal-fired power stations in South Africa. The three stage heat treatment cycle of the FV520B turbine blades consists of homogenisation at 1020°C for 30 minutes, solution treatment at 790°C for two hours and precipitation hardening at 545°C for six hours. In this study, the precipitation hardening temperature was varied in the range 430-600°C to investigate how this variation would affect the material and SCC properties. Hardness and tensile testing were performed to obtain mechanical properties while the investigative techniques used to characterise the microstructures were light microscopy, dilatometry, X-Ray Diffraction (XRD), Scanning Electron Microscopy (SEM) and Transmission Electron Microscopy (TEM). Stress corrosion susceptibility for the different heat treatment conditions was quantified using U-bend specimens while crack growth rates and threshold stress intensities for SCC (KISCC) were measured using fatigue precracked wedge open loaded (WOL) specimens. Both SCC tests were conducted in a 3.5% NaCl environment maintained at 90°C. XRD results revealed the presence of reverted austenite in the higher tempered specimens due to the precipitation hardening temperature being close to the Ac1 temperature for the material. The presence of reverted austenite was shown to adversely affect mechanical strength and hardness which decreased with increasing precipitation hardening temperature. Light and electron microscopy (SEM and TEM) revealed the presence of Cr-rich precipitates along the prior austenite grain boundaries in all tested heat treatment conditions. The propensity, quantity and size of the Cr-rich precipitates increased as the specimen temper temperature increased. SCC susceptibility was shown to be dependent upon yield strength and decreased as precipitation hardening temperature increased with specimens in the overaged condition showing no cracking after more than 5000 hours in the test environment. WOL testing only produced cracking in the three highest strength specimens after 2000 hours. Crack growth rates and threshold stress intensities were found to be dependent on yield strength and decreased with increasing precipitation hardening temperature. Analysis of fracture surfaces revealed crack propagation along prior austenite grain boundaries in all test heat treatment conditions indicating intergranular stress corrosion cracking (IGSCC) as the dominant cracking mechanism.